Enhancing optical properties of WLEDs with LaOF:Eu3+&SiO2 application - Phuc Dang Huu; My Hanh Nguyen Thi (Institute of Advanced Engineering and Science, 2022)
After many efforts, the core-shell nanostructure of LaOF:Eu3+ and SiO2 that emits bright red radiation can be fabricated by simple solvothermal application succeeded by heat treatment. The resulted particles from the fabrication process are small in size, able to demonstrate circular form more efficient and prevent stacking. Photoluminescence (PL) emission spectra exhibits intense peaks at 593 nm, 611 nm, 650 nm corresponds to 5D0 – more than 7FJ (J = 0, 1 and 2) Eu3+ transitions respectively. The spectral intensity parameters and Eu-O ligand behaviors are estimated by means of Judd-Ofelt (J-O) theory. CIE co-ordinates are found to be (x = 0.63, y = 0.36) which is very close to standard NTSC values (x = 0.67, y = 0.33). CCT value is 3475 K which is less than 5000 K, as a result this phosphor is suitable for warm light emitting diodes. The optimized core-shell SiO2 (coat III)@LaOF:Eu3+ (5 mol%) was used as a fluorescent labeling marker to identity latent fingerprints on both porous and non-porous surfaces. The fingerprints results are highly sensitive, selective and also has no obstruction caused by the back-ground which supports level-I to level-III fingerprint ridge recognition. The experiments outcomes suggest that the enhancements brought by the core-shell NS structure can be further examined to apply in forensic and solid state lightning applications.